Negative thermal quenching of photoluminescence in a copper–organic framework emitter. Issue 80 (9th September 2020) - Wu, Ting; Jiang, Shenlong; Samanta, Pabitra Narayan; Xie, Yangbin; Li, Jipeng; Wang, Xiaoling; Devashis, Majumdar; Gu, Xiangwei; Wang, Yusong; Huang, Wei; Zhang, Qun; Leszczynski, Jerzy; et al.
Abstract : This work reports the observation of the NTQ effect in a copper–organic framework emitter through delocalization–localization transition of its imidazole ligand. Abstract : Negative thermal quenching (NTQ), an abnormal phenomenon that the intensity of photoluminescence (PL) increases with increasing temperature, has essentially been restricted to either bulk semiconductors or very low temperatures. Here, we report a delayed fluorescence copper–organic framework exhibiting negative thermal quenching (NTQ) of photoluminescence, which is driven by the fluctuation between the localized and delocalized form of its imidazole ligand. The process is completely reversible on cooling/heating cycles. This study opens a new avenue to explore the electronically switchable NTQ effect in coordination networks and further to develop the NTQ-based light-emitting diodes.